2013
DOI: 10.1002/dvdy.24082
|View full text |Cite
|
Sign up to set email alerts
|

Novel animal pole‐enriched maternal mRNAs are preferentially expressed in neural ectoderm

Abstract: Background: Many animals utilize maternal mRNAs to pre‐pattern the embryo before the onset of zygotic transcription. In Xenopus laevis, vegetal factors specify the germ line, endoderm, and dorsal axis, but there are few studies demonstrating roles for animal‐enriched maternal mRNAs. Therefore, we carried out a microarray analysis to identify novel maternal transcripts enriched in 8‐cell‐stage animal blastomeres. Results: We identified 39 mRNAs isolated from 8‐cell animal blastomeres that are >4‐fold enriched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 70 publications
3
21
3
Order By: Relevance
“…Animal pole transcripts are expressed primarily in the Continued neural ectoderm at later developmental stages, as previously described ( Fig. S1C) (Grant et al, 2014). MetaCore (GeneGo) direct interaction pathway analysis did not reveal integrated networks among the animal pole-enriched RNAs.…”
Section: Novel Mrnas Enriched At the Animal Polesupporting
confidence: 76%
“…Animal pole transcripts are expressed primarily in the Continued neural ectoderm at later developmental stages, as previously described ( Fig. S1C) (Grant et al, 2014). MetaCore (GeneGo) direct interaction pathway analysis did not reveal integrated networks among the animal pole-enriched RNAs.…”
Section: Novel Mrnas Enriched At the Animal Polesupporting
confidence: 76%
“…In fact, transfer of total RNA from neural precursor blastomeres can cause epidermis precursor blastomeres to contribute to ectopic neural tubes (Hainski and Moody, 1992). Although several screens have identified animal hemisphere specific maternal transcripts (e.g., Cha et al, 2012; Bates et al, 2013; Grant et al, 2014), they have not identified the specific gene product(s) responsible for instructing cleavage stage blastomeres to autonomously express a neural fate.…”
Section: Introductionmentioning
confidence: 99%
“…Fragment ions were detected in the ion trap with rapid scan rate with the following settings: maximum IT, 50 ms; AGC, 5 × 10 4 counts; microscans, 1. Multinotch MS 3 fragmentation was triggered on the top 10 MS 2 fragments with HCD in nitrogen (65% NCE). MS 3 spectra were acquired at 15,000 FWMH in the orbitrap (maximum IT, 120 ms; AGC, 1 × 10 5 counts; microscans, 1).…”
Section: Methodsmentioning
confidence: 99%
“…Multinotch MS 3 fragmentation was triggered on the top 10 MS 2 fragments with HCD in nitrogen (65% NCE). MS 3 spectra were acquired at 15,000 FWMH in the orbitrap (maximum IT, 120 ms; AGC, 1 × 10 5 counts; microscans, 1). Fragment ions were dynamically excluded for 60 s before being reconsidered for fragmentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation